1998
DOI: 10.1111/j.1600-0749.1998.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma × Macrophage Fusion Hybrids Acquire Increased Melanogenesis and Metastatic Potential: Altered N‐Glycosylation as an Underlying Mechanism

Abstract: We recently reported that a majority of hybrids generated in vitro between weakly metastatic mouse Cloudman S91 melanoma cells and human or mouse macrophages showed enhanced metastatic potential. With few exceptions, hybrids with enhanced metastatic potential also had elevated basal melanin content and increased responsiveness to MSH compared to parental cells. Here we investigated the hybrid melanotic phenotype in more detail, comparing the pigmentary systems of hybrids and parental Cloudman S91 cells by seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 58 publications
7
28
0
Order By: Relevance
“…4B). These results on LAMP-1 gel migration were similar to previous studies on treatment of high metastatic hybrids with Swainsonine, a GnT-V inhibitor (Dennis et al, 1987;Sodi et al, 1998). Together the results indicated that 5-Aza-dC decreased LAMP-1 glycosylation through an inhibition GnT-V activity.…”
Section: Effects Of 5-aza-dc On Lamp-1 Migration In Elctrophoretic Gelssupporting
confidence: 93%
See 2 more Smart Citations
“…4B). These results on LAMP-1 gel migration were similar to previous studies on treatment of high metastatic hybrids with Swainsonine, a GnT-V inhibitor (Dennis et al, 1987;Sodi et al, 1998). Together the results indicated that 5-Aza-dC decreased LAMP-1 glycosylation through an inhibition GnT-V activity.…”
Section: Effects Of 5-aza-dc On Lamp-1 Migration In Elctrophoretic Gelssupporting
confidence: 93%
“…Besides, GnT-V-associated other phenotypes like increased potential to melanin synthesis and dendrite formation, as mentioned earlier (Rachkovsky et al, 1998;Sodi et al, 1998), was also found to be inhibited during this treatment (not shown). While these effects point to DNA methylation as a regulator of GnT-V expression, no methylation differences in the promoter region were detected between the high and low-metastatic hybrids before and after bisulfite treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In summary, the host-tumor cell hybrid lung metastasis showed the same characteristics as macrophage-melanoma hybrids experimentally fused in vitro, regarding aneuploidy, chemotaxis, enhanced pigmentation, and high levels of autophagy. This was also a characteristic of another spontaneous melanoma-host hybrid described previously ("PADA") [18][19][20] Thus, experimental macrophage-melanoma hybrids in cell culture and spontaneous host-melanoma hybrids arising in vivo and adapted to culture all appeared to show constitutive autophagy without autophagic death. It is important to note that this occurred in cell culture under normoxic conditions and ample nutrients indicating that hybrids expressed the aerobic glycolysis pathway (the Warburg effect) that includes autophagy [42][43][44][45][46][47][48].…”
Section: Spontaneous Fusion In Vivo and Autophagymentioning
confidence: 67%
“…Curiously, in melanoma the most metastatic clones tended to be highly melanized compared to parental melanoma cells or weakly metastatic hybrids as described below ( Fig. 8.4) [19,20]. This was subsequently explained by the acquisition of macrophage glycosylation patterns involving β1,6-branched oligosaccharides that were associated with many phenotypic changes, including pigmentation [21] In two separate rounds of isolation, a total of 75 clones of PEG-fused macrophage-melanoma hybrids were isolated in vitro.…”
Section: Macrophage-melanoma Fusion In Vitro Generates Altered Gene Ementioning
confidence: 99%